Integrating Digital Technology to Improve Motivation and Academic Achievement in Elementary Social Studies: A Mixed-Method Study in Indonesia - Purwantini, Rina; Wijayati, Ida Wahyu (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the integration of digital technology in improving students' motivation and learning achievement in social studies subjects at primary schools in Indonesia. Using a mixed methods approach, this study analyzed secondary data from 15 primary schools with a total of 115 students. The results of the analysis showed an increase in student motivation scores from 2.3 to 3.1, as well as an increase in academic scores from 67.8 to 79.3 after the implementation of digital tools in learning. Based on the SAMR and TPACK frameworks, the majority of schools are still at the Substitution and Augmentation stages. The use of apps such as Canva, Kahoot and Google Earth proved effective in increasing students' engagement and understanding of the material. In addition, the increase in learning motivation can be explained through the ARCS model that emphasizes aspects of attention, relevance, confidence, and satisfaction. Therefore, this study recommends a phased implementation strategy, continuous teacher training, curriculum flexibility, as well as the development of an assessment system that supports inclusive and sustainable digital learning.